2021
DOI: 10.33541/jet.v7i2.2738
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kahoot! Game in Teaching Reading Comprehension Achievement

Abstract: Kahoot! Game is one of the advancements in learning technology. It can facilitate and motivate the students for being active and understanding the content of the text. This study aimed to find out whether there is or not any significant difference between the students who are taught by using Kahoot! Game and the students who are taught by using conventional game and to find out the impact of using Kahoot!. Altogether in this study, the writer used mixed-method and explanatory sequential mixed method design whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…As explained by the researchers (Ronimus et al, 2019;Berry, 2021;Barcomb & Cardoso, 2020;Yürük, 2020) stated in their study that experimental group showed significant improvements in pronunciation skill than the control group which showed higher cognitive engagement. Additionally, the researchers go on to point out that usage of digital games as a learning media can maximizes the language learning which will help to assist students' reading comprehension skill in English learning (Marsa et al, 2021;Pahamzah et al, 2020;Tan et al, 2019;Korkmaz & Öz, 2021). According to Marsa et al (2021); Tan et al (2019), they disputed that instead of hardcopy materials, the learners were more likely reading on the mobile platform.…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%
See 3 more Smart Citations
“…As explained by the researchers (Ronimus et al, 2019;Berry, 2021;Barcomb & Cardoso, 2020;Yürük, 2020) stated in their study that experimental group showed significant improvements in pronunciation skill than the control group which showed higher cognitive engagement. Additionally, the researchers go on to point out that usage of digital games as a learning media can maximizes the language learning which will help to assist students' reading comprehension skill in English learning (Marsa et al, 2021;Pahamzah et al, 2020;Tan et al, 2019;Korkmaz & Öz, 2021). According to Marsa et al (2021); Tan et al (2019), they disputed that instead of hardcopy materials, the learners were more likely reading on the mobile platform.…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%
“…Additionally, the researchers go on to point out that usage of digital games as a learning media can maximizes the language learning which will help to assist students' reading comprehension skill in English learning (Marsa et al, 2021;Pahamzah et al, 2020;Tan et al, 2019;Korkmaz & Öz, 2021). According to Marsa et al (2021); Tan et al (2019), they disputed that instead of hardcopy materials, the learners were more likely reading on the mobile platform. Most probably, this is due to the digital games such as Quizizz and Kahoot!…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Kahoot! application is classified as game based student's response since teacher could manage and design the game based on the topic and material learned, then students are able to response and take part in the game (Marsa et al, 2021).…”
Section: Kahoot! Applicationmentioning
confidence: 99%